FOREIGN IN IMPROVING REGIONAL INNOVATION POLICY (Marketing Journal, 2025)
This article examines the possibilities of institutional adaptation of foreign experiences in improving regional innovation policy. The study analyzes the innovation policy models of the European Union, South Korea, China, and Finland, identifying mechanis ms for their effective integration at the regional level. Special attention is given to aligning these international practices with the context of Uzbekistan —particularly the Namangan region —by focusing on governance modernization, strengthening institutio nal cooperation between the state, academia, and business, and enhancing innovation infrastructure. The article explores institutional barriers, legal harmonization mechanisms, and the socio -economic conditions influencing policy adaptation. As a result, a conceptual model for institutional adaptation is proposed to improve regional innovation systems and foster sustainable innovation -driven growth.
Keywords: regional innovation policy; foreign experience; institutional adaptation; regional economy; Triple Helix model; innovation management; cluster policy; Uzbekistan; Namangan region; technopark infrastructure; international integration